TRÂNSITOS, FLUXOS E TEMPORALIDADES: produções de gênero no cotidiano escolar em Pio XII-MA. - LIMA, Rarielle Rodrigues (2019)
The experiences of school daily constructed by the subjects allow to know the tangle of discourses that circulate in the school spaces. These speeches that, combined with practices, direct and engender behaviors, individuals and processes of subjectivation and / or subjection. In this sense, this thesis aims to understand processes of gender production in daily school, in the municipality of Pio XII, between 2016 and 2019, in two High School Centers. I build in ethnographic weaving the events that are analyzed here, approaching some aspects of the poststructuralist perspective, present in the works of Judith Butler, Teresa de Lauretis and Michel Foucault, mainly, seeking to problematize the processes of crystallization and naturalization of the genre. For this, I highlight statements that are dispersed in this context, among the various actors present in schools and, at the same time are interconnected, as they intend to homogenize certain discursive uniformities, displacing, updating and reiterating certain understandings and recognition of the other and of others. itself as subject, as effects of the experiences produced in this context.